PERAMALAN JUMLAH WISATAWAN AUSTRALIA YANG BERKUNJUNG KE BALI MENGGUNAKAN MULTIVARIAT FUZZY TIME SERIES - SATRIA, I MADE CANDRA; SUKARSA, I KOMANG GDE; JAYANEGARA, KETUT (E-Jurnal Matematika, 2015)
The aim of this paper is to forecast the numbers of Australian tourist to Bali using multivariate fuzzy time series method (MFTS). MFTS method is development from fuzzy time series (FTS). The defferent betwen FTS and MFTS method is showed by factor in used. In FTS method using one factor, but in MFTS method using more than one factor. In this peper there was three factor used in this research, it was number of Australian tourist, Indonesian Inflation, and change rate of AUD to IDR. At the beginning, the speed of each factor was calculated. For each factor given weight, 0,999 for numbers of Australian tourist, -0,90 for Indonesian inflation, and 0,21 for change rate of AUD to IDR. The result showed that Australian tourist at July 2014 would visit Bali as much 91.056 tourist, with average error rate 6.87%.
Keywords: Multivariate Fuzzy Time Series Method; Inflation of Indonesian; Change Rate of AUD to IDR; Australian tourist